The therapeutic importance of isoniazid metabolism in elderly patients - Walubo, Andrew (Division of Clinical Pharmacology, 2018)
This is a study of the role of oxygen free radicals in isoniazid induced toxicity and its implications on the safety of isoniazid containing regimens in elderly patients. During isoniazid metabolism, toxic metabolites are produced which, together with isoniazid, may lead to toxicity by mechanism (s) yet unknown. Understanding the mechanism of toxicity is important for effective management and prevention of isoniazid induced toxicity. Elderly patients take priority for this consideration because isoniazid is more toxic in these people. Consequently, "the therapeutic importance of isoniazid metabolism in elderly patients" was found a suitable title for this work. lsoniazid metabolites; acetylisoniazid, monoacetyl-hydrazine and diacetylhydrazine were synthesized and characterized by thin layer chromatography, high performance liquid chromatography (HPLC), ultra-violet absorption spectra and mass spectrometry. Thereafter, these compounds together with hydrazine were used in the subsequent experiments.